A study on the capability of frequency doubling perimetry in the detection of visual field abnormalities in primary open angle glaucoma patients - Abd jalil, Nor fadzillah (2007)
Frequency Doubling Perimetry (FDP) has become a more widely used technique for both screening for glaucoma patients and follow up of glaucomatous field loss. It is thought to be sensitive to glaucomatous visual field loss because it tests a sparse population of retinal ganglion cells (M cell) which comprise approximately I 0% of entire retinal ganglion cells. Therefore it is superior in the detection of early visual field loss in glaucoma patients than other present conventional methods. To detennine the capability of FDP in the detection of visual field abnonnalities in the primary open angle glaucoma (POAG) patients. Prospective, comparative, cross sectional study. A total number of I 50 POAG patients underwent both FDP in screening and threshold mode 30-2 and Humphrey Visual Field (HVF) 30-2 tests in Eye clinic Hospital Universiti Sains Malaysia (HUSM). All patients had a comprehensive ophthalmology assessment including visual acuity, intraocular pressure, cup-disc-ratio measurement and anterior chamber angle assessment. Data analysis including sensitivity, specificity, area under the receiver operating characteristic (ROC) curve and kappa agreement between FOP and HVF was performed using SPSS system version I 2.0. Data from I I 7 POAG patients were analyzed following inclusion, exclusion criteria and reliability of the visual field testing. For FDP in screening mode, when "at least 1 missed point" was used as the definition for abnormal FDP, the sensitivity was high between 92.2% to 96.2% and specificity was between I 4.3% to 19.3%. When "2 or more missed points", was used as definition for abnormal visual field, the sensitivity was 89.5% to 95.0% and specificity between 29.0% to 35.7% was achieved. For FOP in threshold mode and HVF with various definitions for abnormal visual field, the sensitivity was between 83.5% to I 00% and specificity between 0.0% to 50.0%. Kappa value for FOP and HVF was between 0.074 to 0.341 which showed poor to slight agreement. Conclusion: In this study, FOP showed high sensitivity but low specificity in the detection of visual field abnormalities among POAG patients. The new classification for severity of glaucoma with Glaucoma Scoring System 2 (GSS2) and Frequency Doubling Technology Scoring System 2 (FDT SS2) was able to provide immediate and reliable classification for both severity and characteristic of VF defect. Kappa value of poor to slight agreement was obtained between FOP and HVF.